KRITIK TERHADAP UPAYA JOKOWI MENGHAPUS OPOSISI DARI PERSPEKTIF DEMOKRASI MENURUT PANDANGAN CAK NUR - Kristianto Ratu Marius Naben; Alfian Tanggang (Yayasan Literasi Sains Indonesia, 2025)
This article aims to criticize Joko Widodo's efforts, when he was still President of the Republic of Indonesia, to eliminate the opposition from Indonesia from the perspective of democracy according to Cak Nur's view. This study uses a literature study, namely by collecting data from various journals, books, including several news items related to the theme of the article. The results of this study indicate that Jokowi's decision to fatten his coalition is an attempt to eliminate the opposition in Indonesia. This policy has a negative impact on the sustainability of democracy in Indonesia. This is reinforced by Cak Nur's view of the importance of the opposition for a democratic country like Indonesia. Cak Nur believes that the opposition plays a role in maintaining the stability of a nation. Therefore, the opposition cannot be eliminated with any argument. During his administration, Jokowi tried to eliminate the opposition in Indonesia because he actually did not understand the basic principles of democracy and tended to want to strengthen his dominance in the seat of power. Jokowi's fat coalition is a decision that endangers the sustainability of democracy in this country, because the vital functions of the opposition cannot be carried out.